Differential Methylation of Genomic Regions Associated with Heteroblasty Detected by M&M Algorithm in the Nonmodel Species Eucalyptus globulus Labill. (30th March 2016) - Hasbún, Rodrigo; Iturra, Carolina; Bravo, Soraya; Rebolledo-Jaramillo, Boris; Valledor, Luis
Abstract : Epigenetic regulation plays important biological roles in plants, including timing of flowering and endosperm development. Little is known about the mechanisms controlling heterochrony (the change in the timing or rate of developmental events during ontogeny) in Eucalyptus globulus . DNA methylation has been proposed as a potential heterochrony regulatory mechanism in model species, but its role during the vegetative phase in E. globulus has not been explored. In order to investigate the molecular mechanisms governing heterochrony in E. globulus, we have developed a workflow aimed at generating high-resolution hypermethylome and hypomethylome maps that have been tested in two stages of vegetative growth phase: juvenile (6-month leaves) and adult (30-month leaves). We used the M&M algorithm, a computational approach that integrates MeDIP-seq and MRE-seq data, to identify differentially methylated regions (DMRs). Thousands of DMRs between juvenile and adult leaves of E. globulus were found. Although further investigations are required to define the loci associated with heterochrony/heteroblasty that are regulated by DNA methylation, these results suggest that locus-specific methylation could be major regulators of vegetative phase change. This information can support future conservation programs, for example, selecting the best methylomes for a determinate environment in a restoration project.